U‐shaped association of vigorous physical activity with risk of metabolic syndrome in men with low lean mass, and no interaction of physical activity and serum 25‐hydroxyvitamin D with metabolic syndrome risk. Issue 4 (8th April 2020) - Yeap, Bu B.; Dedic, Deila; Budgeon, Charley A.; Murray, Kevin; Knuiman, Matthew W.; Hunter, Michael; Zhu, Kun; Cooke, Brian R.; Lim, Ee M.; Mulrennan, Siobhain; Walsh, John P.; Green, Daniel J.
Abstract: Background: There is uncertainty over how lean mass, physical activity (PA) and 25‐hydroxyvitamin D (25‐OH‐D) status interact on metabolic syndrome (MetS) risk in adults. Aims: To test the hypothesis that these factors additively influence MetS risk. Methods: Four thousand eight hundred and fifty‐eight adults (54.6% female) mean ± SD age 58.0 ± 5.8 years, body mass index 28.1 ± 4.8 kg/m 2, resident in Busselton, Western Australia. PA assessed by questionnaire (all/total and vigorous), lean mass using dual energy X‐ray absorptiometry (% total body mass), serum 25‐OH‐D via immunoassay, analysed using multivariable logistic regression. Results: In men, lower total PA was associated with MetS (no vs >24 h/week odds ratio (OR) = 3.1; ≤8 vs >24 h/week OR = 1.8, both P < 0.001), as was lower lean mass (low vs high OR = 20.4; medium vs high OR = 7.4, both P < 0.001). Men with low lean mass exhibited a U‐shaped relationship of vigorous PA with MetS risk (covariate‐adjusted: 0 vs 4–8 h/week OR = 2.1, P = 0.037; >12 vs 4–8 h/week OR = 4.3, P = 0.002; interaction P = 0.039). In women, low PA (0 vs >24 h/week OR = 2.1, P = 0.003) and lean mass (low vs high OR = 13.1; medium vs high OR = 7.2, both P < 0.001) were associated with MetS risk. Low 25‐OH‐D status was associated with MetS in men (low vs high OR = 4.1; medium vs high OR = 2.3, both P < 0.001) and women (OR = 3.5 and 2.1 respectively, both P < 0.001) with no PA interaction. Conclusions: Men and women with high lean mass have low risk of MetS regardless of PA. Low lean mass identifies men who may benefit most from increasing PA, with an optimal level associated with lowest risk. 25‐OH‐D and PA do not interact on MetS risk.